Preparation method and application of Zr-crab shell powder composite material

By using Zr-crab shell powder composite as a catalyst, the problems of high energy consumption and safety hazards in traditional furfural hydrogenation methods are solved, and efficient catalytic selective hydrogenation of furfural is achieved, which reduces production costs and by-products, and has good economic and environmental benefits.

CN119633792APending Publication Date: 2025-03-18WUHAN UNIV OF SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411747782.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-02
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

The traditional furfural hydrogenation method uses high pressure hydrogen, which leads to high energy consumption and safety risks, and has high catalyst production costs.

Method used

The Zr-crab shell powder composite was used as a catalyst to obtain purified α-crab shell powder through pretreatment, and the Zr-crab shell powder composite was synthesized by hydrothermal method to prepare furfuryl alcohol for catalytic selective hydrogenation of furfural.

Benefits of technology

Catalyzed selective hydrogenation of furfural at lower temperatures, 95% conversion of furfural and 99% selectivity of furfural alcohol, reducing by-products and separation and purification costs, and has good economic value and environmental significance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119633792A_ABST
    Figure CN119633792A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method and application of a Zr-crab shell powder composite material, and belongs to the technical field of catalysts, the preparation method of the composite material comprises the following steps: S1, preparing purified alpha-crab shell powder; s2, respectively dissolving ZrCl4 and the purified alpha-crab shell powder obtained in the step S1 into deionized water to prepare solutions, uniformly stirring and mixing the two solutions, transferring the mixed solution into a high-pressure reaction kettle, and putting the high-pressure reaction kettle into a drying oven to obtain a precipitate; s3, alternately washing the precipitate obtained in the step S2 with water and ethanol for 1-5 times, centrifuging, putting into a vacuum drying oven, and drying to obtain the Zr-crab shell powder composite material, the Zr-crab shell powder composite material can be applied to preparation of furfuryl alcohol by catalyzing selective hydrogenation of furfural, the composite material provided by the invention is simple in preparation process, easy to operate, low in cost, high in reaction activity and suitable for industrial production. The method is environment-friendly and pollution-free, uses organic alcohol as a hydrogen source, avoids using high-pressure hydrogen, and can efficiently catalyze furfural to be selectively hydro-converted into furfuryl alcohol at a relatively low temperature.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of catalysts, and in particular to a preparation method of a Zr-crab shell powder composite material and application thereof. Background Art

[0002] With the improvement of people's living standards and the increase of population density, fossil fuels can no longer meet people's needs. Therefore, the development of new renewable energy will become a necessary trend for future development. Biorefining of renewable biomass is a sustainable method for preparing biomass fuels and high value-added products. Furfural is an important platform compound from lignocellulose. A series of chemical substances such as furfuryl alcohol, tetrahydrofurfuryl alcohol, furan, tetrahydrofuran, 2-methylfuran, 2-methyltetrahydrofuran, 1,4-pentanediol, etc. can be produced by selective hydrogenation. Among these chemical substances, furfuryl alcohol is an important chemical raw material that can be used to prepare artificial fibers, pharmaceuticals, crown ethers, furan-based resins, adhesives or liquid biofuels. The traditional method of furfural hydrogenation mainly uses high-pressure hydrogen as a hydrogen source, with high reaction temperature, high energy consumption, and high-pressure hydrogen has great danger. Therefore, the development of organic matter as a hydrogen source to catalyze furfural to prepare a new catalytic system for furfuryl alcohol in one step has great research significance and industrial prospects. Summary of the invention

[0003] In order to solve the above problems, the present invention provides a method for preparing a Zr-crab shell powder composite material and its application, and the present invention is achieved through the following technical solutions.

[0004] A method for preparing a Zr-crab shell powder composite material comprises the following steps:

[0005] S1, preparing purified α-crab shell powder, comprising the following sub-steps:

[0006] S11, adding α-crab shell powder to the sodium hydroxide solution, stirring for 24 hours, filtering out the sample, and washing the sample with deionized water until it is neutral;

[0007] S12, adding hydrochloric acid solution to the sample prepared in step S11, stirring for 24 hours, filtering out the sample, and washing the sample with deionized water until it is neutral;

[0008] S13, adding sodium hydroxide solution to the sample prepared in step S12 and stirring and filtering, washing until neutral;

[0009] S14, adding hydrogen peroxide solution to the sample prepared in step S13, bleaching at 60-100° C. for 1-3 hours, and washing with deionized water until neutral;

[0010] S15, covering the sample prepared in step S14 with tin foil, placing it in an oven at 40-100° C. for drying, and grinding the dried sample with a grinder to obtain purified α-crab shell powder;

[0011] S2, ZrCl 4 and the purified α-crab shell powder obtained in step S1 are dissolved in deionized water to prepare solutions, the two solutions are stirred and mixed evenly, and then transferred to a high-pressure reactor and placed in an oven to obtain a precipitate;

[0012] S3, washing the precipitate obtained in step S2 with water and ethanol alternately for 1-5 times, centrifuging and placing in a vacuum drying oven, and drying to obtain a Zr-crab shell powder composite material.

[0013] Preferably, in the step S11, 400 g of α-crab shell powder is added to 4 to 5 L of 5% sodium hydroxide solution; in the step S12, 4 to 5 L of 7% hydrochloric acid solution is added; in the step S13, 5% sodium hydroxide solution is added; in the step S14, 4 to 5 L of 4% hydrogen peroxide solution is added, and bleaching is carried out for 1 to 2 hours.

[0014] Preferably, in step S2, ZrCl 4 and purified α-crab shell powder are dissolved in 15 ml and 50 ml of deionized water respectively; the oven temperature is raised to 100-200° C. and maintained for 10-14 h.

[0015] Preferably, in step S2, ZrCl 4 The mass ratio of α-crab shell powder to α-crab shell powder is 1:3, 1:2, 1:1, 2:1, 3:1 or 5:1.

[0016] Preferably, in step S3, the precipitate is washed alternately with water and ethanol for 2 to 3 times, and after centrifugation, is placed in a vacuum drying oven at 40 to 120° C. and maintained for 10 to 14 hours.

[0017] Application of Zr-crab shell powder composite material in catalytic selective hydrogenation of furfural to furfuryl alcohol.

[0018] The invention discloses an application method of Zr-crab shell powder composite material in catalyzing the selective hydrogenation of furfural to prepare furfuryl alcohol. The application method is as follows: using any one of methanol, ethanol, n-propanol, tert-butanol, isopropanol, 2-butanol and 3-pentanol as a solvent to prepare a furfural solution; adding the Zr-crab shell powder composite material to the furfural solution; the reaction temperature is 40 to 140° C., and the reaction time is 0.3 to 4 hours to prepare furfuryl alcohol.

[0019] Preferably, the reaction temperature is 100° C. and the reaction time is 1 h.

[0020] The beneficial effect of the present invention is that the present invention uses discarded crab shell powder as a raw material, obtains purified α-crab shell powder material through pretreatment, and synthesizes a Zr-crab shell powder composite material through a hydrothermal method, thereby reducing the production cost of the catalyst. The Zr-crab shell powder composite material has a large specific surface area and high reaction activity, and can catalyze the selective hydrogenation of furfural at a relatively low temperature, achieving a conversion rate of 95% of furfural and a selectivity of 99% of furfuryl alcohol, which greatly improves the efficiency of the reaction, reduces by-products, reduces separation and purification costs, and has good economic value and environmental significance. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] In order to more clearly illustrate the technical solution of the present invention, the drawings required for use in the description of the specific implementation methods will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0022] Figure 1 : Characterization photos of the Zr-crab shell powder composite material prepared in Example 1;

[0023] Figure 2 : XRD diagram of the Zr-crab shell powder composite material obtained in Examples 1-3 and Example 5. DETAILED DESCRIPTION

[0024] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0025] Example 1

[0026] A method for preparing a Zr-crab shell powder composite material comprises the following steps:

[0027] S1, preparing purified α-crab shell powder, comprising the following sub-steps:

[0028] S11, adding 400 g of α-crab shell powder to 5 L of 5% sodium hydroxide solution, stirring for 24 h, filtering out the sample, and washing the sample with deionized water until it is neutral;

[0029] S12, adding 5 L of 7% hydrochloric acid solution to the sample prepared in step S11, stirring for 24 hours and filtering out the sample, and washing the sample with deionized water until it is neutral;

[0030] S13, adding 5 L of 5% by mass sodium hydroxide solution to the sample prepared in step S12 and stirring and filtering, washing until neutral;

[0031] S14, adding 5 L of 4% hydrogen peroxide solution to the sample prepared in step S13, bleaching at 80° C. for 2 h, and washing with deionized water until neutral;

[0032] S15, covering the sample prepared in step S14 with tin foil, placing it in a 60° C. oven for drying, and grinding the dried sample with a grinder to obtain purified α-crab shell powder;

[0033] S2, 3gZrCl 4 and 1 g of the purified α-crab shell powder obtained in step S1 were dissolved in 15 ml and 50 ml of deionized water respectively to prepare solutions, the two solutions were stirred and mixed evenly, and then transferred to a high-pressure reactor, placed in an oven, heated to 120° C., reacted for 12 h, and then taken out and allowed to cool naturally to obtain a precipitate;

[0034] S3, washing the precipitate obtained in step S2 with water and ethanol alternately for 2 to 3 times, centrifuging and placing it in a 60° C. vacuum drying oven for 12 hours, and grinding it with a mortar after drying to obtain a Zr-crab shell powder composite material, which is Zr-crab shell powder (3:1).

[0035] Embodiment 2-6

[0036] The difference between Example 2-6 and Example 1 is that ZrCl 4 The mass ratio of Zr to α-crab shell powder was different. Zr-crab shell powder composites with different metal contents were prepared, namely Zr-crab shell powder (1:1), Zr-crab shell powder (1:2), Zr-crab shell powder (1:3), Zr-crab shell powder (2:1), and Zr-crab shell powder (5:1).

[0037] The Zr-crab shell powder composite material obtained in Example 1 was characterized as follows: Figure 1 As shown, Figure 1 a~b are SEM photos of Zr-crab shell powder composite materials. Figure 1 c~g are TEM photos of Zr-crab shell powder composite materials. Figure 1 h~k are mapping photos of Zr-crab shell powder composite materials

[0038] It can be seen from the SEM and TEM photos that the composite material is an irregular spherical structure with a particle size of 100 nm.

[0039] The composite materials prepared in Examples 1-6 were subjected to catalyst performance evaluation. The steps for catalyst performance evaluation are as follows: 50 mg of the composite material, 0.5 mmol of furfural and 50 ml of isopropanol were added to a high-pressure reaction tube, heated and stirred in an oil bath at 100°C, and reacted for 3 hours. The solution in the reaction tube was collected and centrifuged, and the supernatant was taken to measure the furfural conversion rate and furfuryl alcohol yield. The specific experimental parameters and product yields are shown in Table 1.

[0040] Table 1:

[0041]

[0042] It can be seen from Table 1 that with the increase of Zr content, the furfural conversion rate and the yield of furfural alcohol first increased and then decreased. When the ratio of Zr to α-crab shell powder was 3:1, the furfural conversion rate and the yield of furfural alcohol were the largest, proving that the appropriate Zr content is conducive to the selective hydrogenation of furfural to produce furfural alcohol.

[0043] Examples 7-12

[0044] Using Zr-crab shell powder (3:1) composite materials, and using different solvents to prepare furfuryl alcohol, 50 ml of methanol, ethanol, n-propanol, tert-butanol, 2-butanol and 3-pentanol were added as solvents in different high-pressure reaction tubes, and 50 mg of composite materials and 0.5 mmol of furfural were added to different high-pressure reaction tubes, heated and stirred in a 100 ° C oil bath, and reacted for 3 hours. The solution in the reaction tube was collected and centrifuged, and the supernatant was taken to measure the furfural conversion rate and furfuryl alcohol yield. The furfural conversion rate and furfuryl alcohol yield are shown in Table 2.

[0045] Table 2:

[0046] Example Solvents Furfural conversion rate (%) Furfuryl alcohol yield (%) Example 1 Isopropyl alcohol 95 94 Example 7 Methanol 94 0 Example 8 Ethanol 80 8 Example 9 n-Propanol 58 12 Example 10 Tert-Butanol 8 3 Embodiment 11 2-Butanol 70 36 Example 12 3-Pentanol 48 30

[0047] It can be seen from Table 2 that when isopropanol is used as the solvent, the furfural conversion rate and the furfuryl alcohol yield are the highest.

[0048] Examples 13-15

[0049] Furfuryl alcohol was prepared using Zr-crab shell powder (3:1) composite material and isopropanol as solvent. The reaction was completed at different temperatures. The furfural conversion rate and furfuryl alcohol yield are shown in Table 3.

[0050] Table 3:

[0051] Example Temperature(℃) Furfural conversion rate (%) Furfuryl alcohol yield (%) Embodiment 13 40 5 4 Embodiment 14 60 28 12 Embodiment 15 80 54 53 Example 1 100 95 94

[0052] It can be seen from Table 3 that the reaction temperature of 100°C is the optimal temperature for preparing furfuryl alcohol from furfural.

[0053] The preferred embodiments of the present invention disclosed above are only used to help explain the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to only specific implementation methods. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.

Claims

1. A method for preparing a Zr-crab shell powder composite material, characterized in that: The following steps are involved: S1, preparing purified α-crab shell powder, comprising the following sub-steps: S11, adding α-crab shell powder to the sodium hydroxide solution, stirring for 24 hours, filtering out the sample, and washing the sample with deionized water until it is neutral; S12, adding hydrochloric acid solution to the sample prepared in step S11, stirring for 24 hours, filtering out the sample, and washing the sample with deionized water until it is neutral; S13, adding sodium hydroxide solution to the sample prepared in step S12 and stirring and filtering, washing until neutral; S14, adding hydrogen peroxide solution to the sample prepared in step S13, bleaching at 60-100° C. for 1-3 hours, and washing with deionized water until neutral; S15, covering the sample prepared in step S14 with tin foil, placing it in an oven at 40-100° C. for drying, and grinding the dried sample with a grinder to obtain purified α-crab shell powder; S2, dissolving ZrCl4 and the purified α-crab shell powder obtained in step S1 in deionized water to prepare solutions, stirring and mixing the two solutions, transferring the solutions to a high-pressure reactor, and placing the solutions in an oven to obtain a precipitate; S3, washing the precipitate obtained in step S2 with water and ethanol alternately for 1-5 times, centrifuging and placing in a vacuum drying oven, and drying to obtain a Zr-crab shell powder composite material.

2. The method for preparing a Zr-crab shell powder composite material according to claim 1, characterized in that: In the step S11, 400 g of α-crab shell powder is added to 4 to 5 L of 5% sodium hydroxide solution; in the step S12, 4 to 5 L of 7% hydrochloric acid solution is added; in the step S13, 5% sodium hydroxide solution is added; in the step S14, 4 to 5 L of 4% hydrogen peroxide solution is added, and bleaching is performed for 1 to 2 hours.

3. The method for preparing a Zr-crab shell powder composite material according to claim 1, characterized in that: In the step S2, ZrCl4 and purified α-crab shell powder are dissolved in 15 ml and 50 ml of deionized water respectively; the oven is heated to 100-200° C. and maintained for 10-14 hours.

4. The method for preparing a Zr-crab shell powder composite material according to claim 1, characterized in that: In the step S2, the mass ratio of ZrCl4 to α-crab shell powder is 1:3, 1:2, 1:1, 2:1, 3:1 or 5:

1.

5. The method for preparing a Zr-crab shell powder composite material according to claim 1, characterized in that: In step S3, the precipitate is washed alternately with water and ethanol for 2 to 3 times, and after centrifugation, is placed in a vacuum drying oven at 40 to 120° C. and maintained for 10 to 14 hours.

6. Use of the Zr-crab shell powder composite material prepared by the method according to any one of claims 1 to 5 in catalyzing the selective hydrogenation of furfural to prepare furfuryl alcohol.

7. A method for using the Zr-crab shell powder composite material prepared by the method according to any one of claims 1 to 5 in catalyzing the selective hydrogenation of furfural to prepare furfuryl alcohol, characterized in that: The application method is as follows: use any one of methanol, ethanol, n-propanol, tert-butanol, isopropanol, 2-butanol and 3-pentanol as a solvent to prepare a furfural solution; add the Zr-crab shell powder composite material to the furfural solution; the reaction temperature is 40-140°C, the reaction time is 0.3-4h, and furfuryl alcohol is prepared.

8. The method for using the Zr-crab shell powder composite material as claimed in claim 7 in catalyzing the selective hydrogenation of furfural to prepare furfuryl alcohol, characterized in that: The reaction temperature was 100°C and the reaction time was 1 h.